Relationships of age of menarche, frequency and duration of kunyit asam consumption and dysmenorrhea - Prasetyowati, Sebrina Andri; Surjadi, Lily Marliany (Jurnal Biomedika dan Kesehatan, 2022)
BACKGROUNDPuberty is intimately associated with adolescence, one of which is the first menstrual period. Young women frequently have dysmenorrhea as a result of menarche. Dysmenorrhea that isn't medicated appropriately might make it difficult for young women to go about their daily lives. Consuming kunyit asam is one solution to relieve the intensity of dysmenorrhea pain. This study aims to determine whether the consumption of kunyit asam and its regularity during menstruation can lower abdominal pain in dysmenorrhea. METHODSIn October 2021, a cross-sectional survey was conducted at the Yayasan Indocement Middle School in Bogor, West Java. Cluster random sampling was used to collect data from 108 junior high school students who completed the Form Frequency Questionnaire (FFQ) questionnaire to determine the frequency and duration of kunyit asam consumption and the Numeric Rating Scale (NRS) questionnaire to reduce the severity of dysmenorrhea pain. The Chi-Square test was used to examine the data, with the level of <0.05 as the significance level. RESULTSOf 108 respondents, most of them experienced menarche at >11 years old (90.74%), always take kunyit asam solution (57.41%) with duration >3 months (74.07%) and did not have menstrual pain (88.89%). In junior high school adolescents, a significant correlation was discovered between the frequency and the duration of kunyit asam consumption and dysmenorrhea (p=0.016, p=0.007). CONCLUSIONIn junior high school students, there is a correlation between the frequency and duration of kunyit asam consumption and dysmenorrhea. KEYWORDS: Regularity, Length, Kunyit Asam Solution, Dysmenorrhea, Teenage Girls